Penerapan Pidana Adat dan Pidana KUHP Terhadap Pelaku Tindak Pidana Zina Dikaitkan Dengan Peran Kepolisian â€ ( Studi Kasus Wilayah Hukum Persukuan Domo Air Tiris dan Kapolres Kampar) - Rido i, Muhammad; ', Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Customary law has roots strong value to the social behavior and cultural patterns. So in practice, people are more likely to use customary law to resolve the case as well as in the materials make the guidelines and norms to regulate legal relations. Indonesia, which consists of various customs very terliahat existence that customary law and traditional criminal law is still alive in their respective regions. Particularly in the Kampar Regency Tribal Domo Air Tiris customary criminal law is still in use by the public in solving the crime of adultery. To the authors interested melakaukan ilmia research as a work in the form of a thesis titled "Implementation of Adat Criminal Penal Code and Criminal In Against Perpetrators of the Crime of Adultery Associated With Role of Police (Case Study Regional Water Domo Tribal Customary Law And Police Tiris Kampar)".The purpose of this study is to determine: first how the concept of adultery a criminal offense under criminal law and criminal customary in the Criminal Code. Both how the settlement process adultery a criminal offense under criminal law and criminal customary in the Criminal Code. Third how the position of indigenous criminal decisions in criminal cases of adultery. In this penelilitian author uses the method of writing juridical empirical (sociological) the approach to maslaah to see the legal norms in force, connected with the facts in the problems encountered.From the results of this study concluded that. The concept of the crime of adultery under criminal law customary everyone whose marital relationship either bound or not bound legitimate marital relationship with the other party. The concept of adultery a criminal offense under the Criminal Code of Article 284 by the Criminal Code. The process of settlement of the crime of adultery under customary law uses the concept bajanjang naiak, batanggo down, which first performed amicably (mamak cornerstone), mamak pisoko, and finally resolved mamak village level. Completion by the Criminal Code, namely, receiving reports, foreclosure marriage book, calling as witnesses, determination of the suspect, ending with mediation. Position customary verdict against the crime of adultery in Indonesian positive law recognized by law because in the process of completion te was achieved peace on both sides. Dissatisfaction in ruling customary police complaint can proceed to the commencement of the investigation stage.Keywords: Indigenous Customary Law-Criminal-Crime Adultery.